Cost Recovery of Congested Infrastructure under Market Power - Erik T. Verhoef (Tinbergen Institute, 2012)
The famous Mohring-Harwitz theorem states that, under certain technical conditions, the degree of self-financing of congested infrastructure is equal to the elasticity of the capacity cost function in the optimum, so that under neutral scale economies exact self-financing applies. Although the theorem has been proven to remain valid for various extensions of the basic set-up for which it was originally derived, it breaks down when the infrastructure is used by operators with market power when competing in Cournot fashion, the case in point often being oligopolistic airlines at a congested airport. This paper proposes a regulatory scheme, not involving lump-sum payments or budget constraints in the optimal pricing problem, that restores self-financing for congested infrastructure for this market form. What is more, under the proposed scheme, exact self-financing applies independent of the elasticity of the capacity cost function. The result remains true both for the case where operators treat the tolls parametrically, and for 'manipulable' tolls, designed to account for the fact that operators with market power can be expected to be aware of, and exploit, the fact that toll are not truly parametric, but instead depend on their own behaviour.
urn:NBN:nl:ui:31-1871/38460
Keywords: R41; R48; D62; 330; Congestion pricing; capacity choice; self-financing infrastructure; market power; airport congestion; Bottleneck; Infrastrukturfinanzierung; Flughafenbau; Luftverkehrsgesellschaft; Monopolistischer Wettbewerb; Duopol; Theorie